Given equation is "y'''' +2y'''+11y''+18y'+18y=0"
Making auxiliary equation, "m^4 + 2m^3 + 11m^2 +18m + 18 = 0"
Roots of the equation are "m = -1\\pm i, \\pm3i"
So equation will be "y = e^{-x} (c_1 cosx + c_2sinx) + c_3cos3x+c_4sin3x"
applying boundary conditions "y(0) = 2,y'(0)=3,y''(0)=-11,y'''(0)=-23"
simply putting x=0 in equation, we obtain
"2 = c_1 + c_3" (1)
differentiating y once and applying condition , we get
"y' = -e^{-x}\\left(c_1\\cos \\left(x\\right)+c_2\\sin \\left(x\\right)\\right)+e^{-x}\\left(-c_1\\sin \\left(x\\right)+c_2\\cos \\left(x\\right)\\right)-3c_3\\sin \\left(3x\\right)+3c_4\\cos \\left(3x\\right)"
"3 = -c_1 + c_2 + 3c_4" (2)
differentiating again and applying conditions
"y'' = 2c_1e^{-x}\\sin \\left(x\\right)-2c_2e^{-x}\\cos \\left(x\\right)-9c_3\\cos \\left(3x\\right)-9c_4\\sin \\left(3x\\right)"
"-11 = -2c_2-9c_3" (3)
differentiating again and applying conditions
"y'''=2c_1\\left(-e^{-x}\\sin \\left(x\\right)+e^{-x}\\cos \\left(x\\right)\\right)-2c_2\\left(-e^{-x}\\cos \\left(x\\right)-e^{-x}\\sin \\left(x\\right)\\right)+27c_3\\sin \\left(3x\\right)-27c_4\\cos \\left(3x\\right)"
"-23 = 2c_1+2c_2-27c_4" (4)
solving equation 1,2,3 and 4,
"c_1=c_2=c_3=c_4 =1"
Then equation will be
"y = e^{-x} ( cosx + sinx) + cos3x+sin3x"
Comments
Leave a comment